2014
DOI: 10.1080/01431161.2014.967889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spatial sampling strategies for ground sampling and validation of MODIS LAI products

Abstract: The development of an efficient ground sampling strategy is critical to assess uncertainties associated with moderate-or coarse-resolution remote-sensing products. This work presents a comparison of estimating spatial means from fine spatial resolution images using spatial random sampling (SRS), Block Kriging (BK), and Means of Surface with Nonhomogeneity (MSN) at 1 km 2 spatial scale. Towards this goal, we focus on the sampling strategies for ground data measurements and provide an assessment of the MODIS LAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…When carrying out spatial interpolation, our results support previous studies who have shown that sampling design can have a considerable impact on the quality and validity of the interpolated mapping produced, e.g. [ 60 ]. The choice of sampling strategies is governed and affected by several factors, including the interpolation approach being used, the human resources available, distance between measurements, and site remoteness and accessibility [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…When carrying out spatial interpolation, our results support previous studies who have shown that sampling design can have a considerable impact on the quality and validity of the interpolated mapping produced, e.g. [ 60 ]. The choice of sampling strategies is governed and affected by several factors, including the interpolation approach being used, the human resources available, distance between measurements, and site remoteness and accessibility [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…The uncertainties in the high‐resolution reference data should ideally be smaller than those in the LAI products (Widlowski, ). In general, both field measurement and transfer function uncertainties need to be considered to improve the reference LAI accuracy (Ding et al, ; R. A. Fernandes et al, ; Garrigues, Lacaze, et al, ; A. H. Li et al, ). Prior to validation, it is important to examine the vegetation distribution within the pixel to check whether the field data are representative of the larger pixel (Fang, Wei, & Liang, ; Nikolov & Zeller, ).…”
Section: Product Validation and Evaluationmentioning
confidence: 99%
“…However, this method has been mostly used in low LAI areas because of the easy saturation of VI and reflectance in high LAI areas. As an alternative, geostatistical techniques have been effective in identifying spatially representative areas and mitigating the spatial mismatch between satellite pixels and reference data (Ding et al, ; Martinez et al, , ). Using sampling schemes adapted to the spatial variability of the LAI (e.g., Validation of Land European Remote sensing Instruments) and by sampling sufficient numbers (>100) of ground measurements, the problem of scale differences in generating the reference data can be partly overcome (Nackaerts et al, ; Richter, Atzberger, et al, ).…”
Section: Product Validation and Evaluationmentioning
confidence: 99%
“…For the Jingyuetan site, an empirical regression approach was also employed using 79 field-measured LAIs and two Landsat8 OLI images to retrieve the LAI maps. An enhanced vegetation index (EVI) was also used [ 40 ].…”
Section: Methodsmentioning
confidence: 99%